2020
DOI: 10.3390/ma13010181
|View full text |Cite
|
Sign up to set email alerts
|

High Specific Capacitance of the Electrodeposited MnO2 on Porous Foam Nickel Soaked in Alcohol and its Dependence on Precursor Concentration

Abstract: In this work, we used the mixed solution of manganese acetate and sodium sulfate to deposit manganese dioxide on the three-dimensional porous nickel foam that was previously soaked in alcohol, and then the effects of solution concentrations on their capacitance properties were investigated. The surface morphology, microstructure, elemental valence and other information of the material were observed by scanning electron microscope (SEM), Transmission Electron Microscope (TEM), X-ray photoelectron spectroscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the recent years, scientists have been paying more and more emphasis to supercapacitors, which are regarded as renewable energy storage devices due to the advantages of rapid charging and discharging, high energy density, power density, outstanding rate performance, and long-term cycling stability performance. [3][4][5][6] Meanwhile, their applications in numerous elds have promising prospects, particularly in hybrid vehicles and military equipment. 7,8 In general, supercapacitors can be classied into two categories depending on the mechanism of energy storagepseudocapacitors (PCs) and electric double-layer capacitors (EDLCs).…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, scientists have been paying more and more emphasis to supercapacitors, which are regarded as renewable energy storage devices due to the advantages of rapid charging and discharging, high energy density, power density, outstanding rate performance, and long-term cycling stability performance. [3][4][5][6] Meanwhile, their applications in numerous elds have promising prospects, particularly in hybrid vehicles and military equipment. 7,8 In general, supercapacitors can be classied into two categories depending on the mechanism of energy storagepseudocapacitors (PCs) and electric double-layer capacitors (EDLCs).…”
Section: Introductionmentioning
confidence: 99%
“…K. M. Racik et al [ 50 ] found good electrochemical performance in their MnO 2 /NiO electrodes while KOH is used as an electrolyte. M. Zhange et al [ 51 ] reported high specific capacitance (529 F/g at 1 A/g) in their electrodeposited MnO 2 supercapacitor on 3D porous Ni foam. From this discussion, it is clear that the incorporation of NiO improves the electrochemical performance of MnO 2 .…”
Section: Introductionmentioning
confidence: 99%